Neurospora Mutant Exhibiting Hyperproduction of Amylase and Invertase - Gratzner, Howard (1969)
A mutant strain of Neurospora crassa has been isolated which is derepressed for amylase and β-fructofuranosidase (invertase). Large amounts of the two enzymes were secreted into the culture medium upon depletion of exogenous carbon source. The resulting increases of the two extracellular enzymes were prevented by actinomycin D, cycloheximide, and glycerol. The starving cells of the mutant strain produced amylase and invertase de novo, as evidenced by incorporation of radioactive amino acids into the enzymes. Preliminary genetic studies indicate that these elevated enzyme levels described are due to a single gene mutation.